A hundred things - van der Rijt, Arvid (Taideyliopiston Kuvataideakatemia, 2022)
The artistic component of my Master’s thesis project consisted of an installation called Tempo Dulu, which was exhibited during Kuvan Kevät in 2021. My work was shown at Exhibition Laboratory (B) in the month of May. Tempo Dulu is an installation with sound, moving image, light and objects in a live environment. On an area covering thirty square metres there are plinth-like constructions that are used to present objects, mirrors, video screens, surveillance cameras, flickering lights and hand-made screens. The displayed objects generate images, reflections, shadows and silhouettes, starting a chain of associations as it builds a narrative. Before the spectator’s eyes a diorama unfolds into itself. Trapped in a feedback loop, one is thrown back in the context that only exists in one’s head. Everything that is hidden deep in a culture, shame, sorrow, pride and hope, manifests in various forms on the surface, in the superficial, the mundane, in utensils, in popular culture, in everyday life. At times seemingly trivial and ubiquitous it layers a multiplicity of meaning. This written part of my thesis is a documentation and description of the practical work and offers a personal background that explains some of the topics my work touches upon. I will elaborate on the importance of fiction, narrative and cultural position and explain some of the formal aspects of my work, with a special interest in how things are perceived. This text is not a documentation of my installation in the way that it will give you a crystal clear image of what has been shown. It has a similar strategy as my artistic work Tempo Dulu, which is site- and time- specific, in that it has live elements and offers different viewpoints.
Keywords: fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|